2020
DOI: 10.1002/alz.039145
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic use in dementia: The relationship between neuropsychiatric symptom profiles and adverse outcomes

Abstract: Background Antipsychotic treatments are associated with safety concerns in people with dementia. The authors aimed to investigate whether risk of adverse outcomes related to antipsychotic prescribing differed according to major neuropsychiatric syndromes – specifically psychosis, agitation, or a combination – in order to inform a precision medicine approach to management of key neuropsychiatric symptoms. Method A cohort of 10,106 patients with a diagnosis of dementia was assembled from a large dementia care da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Other studies have reported no increased risk of cerebrovascular events in risperidone or quetiapine users compared with nonusers with dementia. 15,17,19 Similarly, no difference in stroke risk between risperidone vs other antipsychotics or quetiapine vs other antipsychotics was observed in a recent study of people with dementia. 15 Several mechanisms for the association between antipsychotics and strokes have been proposed.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Other studies have reported no increased risk of cerebrovascular events in risperidone or quetiapine users compared with nonusers with dementia. 15,17,19 Similarly, no difference in stroke risk between risperidone vs other antipsychotics or quetiapine vs other antipsychotics was observed in a recent study of people with dementia. 15 Several mechanisms for the association between antipsychotics and strokes have been proposed.…”
Section: Discussionmentioning
confidence: 93%
“…15,17,19 Similarly, no difference in stroke risk between risperidone vs other antipsychotics or quetiapine vs other antipsychotics was observed in a recent study of people with dementia. 15 Several mechanisms for the association between antipsychotics and strokes have been proposed. In addition to blockade of dopamine receptors, different antipsychotics act on serotonergic, histaminergic, muscarinic, and alpha-adrenergic receptors.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This bespoke application is designed to identify medications that are currently prescribed to the patient and was developed through expert annotation, which means that domain experts coded whether the medication prescription was present in a particular document based on pre-defined coding rules and/or their expert experience. 21 This searched for any reference to trazodone (and common mis-spellings or molipaxin, the UK trade name) and comparator drugs, citalopram or mirtazapine, and extracted the date of the record. Any relevant record of the drugs of interest during the study window would be detected by the GATE algorithm so drug exposure was measured longitudinally.…”
Section: Exposurementioning
confidence: 99%